Evolving work, evolving skills: how different forms of further training are used to adapt to technological change depending on task complexity - Seegers, Marco [Verfasser]; Birgit Zeyer-Gliozzo [Verfasser] (My University, 2025)
“Technological transformation is changing the tasks and skill profiles of the workforce in modern Western societies, and participation in further training is often seen as an adaptation strategy. However, the specific types of training used to address the increasing task complexity and technology use remain unclear. This study examines the impact of technology use at work on participation in informal and non-formal further training in Germany, considering the complexity of job tasks. Using data from the German National Educational Panel Study (NEPS), logistic regression models show that a more frequent use of networked digital technology tends to favour participation in informal training while for non-formal training the effect is smaller and insignificant. The expected interaction between technology use and task complexity on participation in non-formal and informal training is not significant. Further analysis suggests that the underlying mechanisms may be more complex and vary by age and sector. Overall, the findings provide initial evidence that non-formal and informal training appear to play different roles in the process of technological change, although further research is needed to validate and understand the underlying dynamics.” (authors’ abstract; BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; G 1.2.3.2 Anforderungen & Bedarfe; L 2.1.1 Informelles Lernen; 370; Arbeitswelt; Technischer Wandel; Anforderungsprofil; Qualifikationswandel; Komplexität; Weiterbildung; Informelles Lernen; Non-formales Lernen; Digitale Medien; Medieneinsatz; Lernerfolg; Nationales Bildungspanel; Learning Analytics